Efektivitas ASEAN+3 dalam Pengakomodasian Kerja Sama Regional Asia Tenggara dan Asia Timur - Deti Sufendi Mahesa Ringga; Ria Nur Fadillah; Tumiri Ali (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
In the life of having state, there are opportunities for cooperation to be carried out to achieve the goals that the country wants. Like human life that forms relationships with other humans as humans should be social beings. Some countries collaborate in one forum to clarify their goals and intentions. Likewise with ASEAN, standing as an organization of one regional region namely Southeast Asia, ASEAN will always face new challenges. The role of ASEAN is to find and prepare a solution. Sometimes, this collaboration must be extended to achieve greater goals according to what ASEAN wants. One of these collaborations is to add other countries such as China, Japan and Korea or more familiarly called ASEAN + 3. Of course, there is a program launched by this collaboration that hope will has an impact on ASEAN + 3 countries. This paper trying to discuss the actions that have been planned or carried out by ASEAN + 3 and see the extent of the effectiveness of this cooperation. ASEAN + 3 has brought wind of hope for their member countries without forgetting the fact that other impacts have caused it. Research from this paper is based on literature sources and looks at the facts as one of the ASEAN + 3 member countries. This paper concludes a number of programs planned by ASEAN + 3 and the extent to which they have been effective. In addition, this paper discusses what impacts ASEAN + 3 will have in the future.